PROGRAM PELATIHAN DENGAN METODE SIMULASI UNTUK FASILITATOR: PENELITIAN AWAL KEMATIAN TENTANG IBU YANG HAMIL, SIAPA YANG BERTANGGUNG JAWAB? - Nuryati Atamimi; Rasimin Bujang Sanmustari; Sofia Retnowati (Jurnal Psikologi, 2002)
Maternal mortality rate in Indonesia is considered relatively high (UNICEF, 1994). It is necessary to make concrete efforts to cut down the number of women who die in the period of their pregnancy, at birth, and in the period of 42 days after birth, either caused by direct effects of pregnancy of birth, or by indirect effects of certain diseases, not to include accidents. Maternal mortality has socially broad impact since the mother’s double functions is cannot be replaced by others. Research has shown that a baby born by a mother who died at the birth, has 90 % possibility to die in the first year of his or her life. This tragedy should not have happened since 80 % of maternal mortality can be prevented (Indonesian Department of Health, 1999). This study is meant to find an alternative method which is reliable and testable to improve the level of initiative (responsive attitudes) of pregnant women and of all elements of the surrounding social institutions to issues related to maternal mortality risk. One to mention is by comparing the use of simulation method (together with poster campaigns) with that of radio-spot broadcast method. The study focuses on several targets, among others are 1) a case study related to the handling of high-risk pregnancy which has so far been done, as a step stone to developing an instrument to change attitude/behavior; 2) constructing an inventory or questionnaire on attitude change which will be used as a measuring instrument in the research to follow; and 3) making instruments to change attitude (in the forms of simulation sheets and posters) of which the effectiveness, validity, and reliability as intervening media will be trained to the simulation facilitators. Developing intervening media in the form of radio-spots will be in the third-year phase of the study, and comparing the two intervening media is to be done in the year afterwards. The third and fourth studies, however, do not manifest since the budget cut is significant in limiting the production of the intervention media. The preliminary study by using in-depth interviews with 56 subjects showed that a great majority of high-risk pregnant women had low level of understanding and initiative to various anticipatory measures needed to face emergency situations in pregnancy period and at birth. A number of social institutions in the surroundings such as neighbors and Village Community Welfare Institutions and health service providers such as Integrated Service Post and Community Health Center had not yet played significant roles. Draft of simulation sheets and posters had been made and tried out according to the plan. The questionnaire has been designed and has been tried out. The training for the facilitators has also been completed in the first year study. Keywords: Simulation method, material mortality.